Confronting the Demise of a Mother Tongue: The Feasibility of Implementing Language Immersion Programs to Reinvigorate the Taiwanese Language - Gijsen, Johan; Liu, Yu-chang (Revue de l'Université de Moncton)

(untitled) (Revue de l'Université de Moncton, 2007)
AbstractIn Taiwan, where Mandarin is the official language, the survival of Taiwanese, the mother tongue of sixty percent of the island’s inhabitants, is threatened. In this article, the authors discuss data from previous and ongoing research on the role of language and the significance of language loss in the quest for a “Taiwanese identity.” Research shows that the dominance of Mandarin over Taiwanese plus the growing support for English in Taiwan are likely indications that current Mandarin/Taiwanese bilingualism is being replaced by Mandarin/English bilingualism. Canadian, Finnish, Basque and Catalonian models of language immersion programs will be proposed as an alternative to Taiwan’s current language policy. The authors argue that such models, when applied to a significant degree in Taiwan’s primary education system, will contribute to strengthening Taiwanese identity, to defending the right of youngsters to receive their education in their Taiwanese mother tongue, and to creating more effective English language training.